Adsorption Characteristics of -Phthalic Acid and its Separation by Resins from Maleic Acid and Fumaric Acid in Wastewater - Fei Zhenghao; Wang Mujun; Chen Jinlong; Sun Yue; Li Aimin; Zhang Quanxing (Adsorption Science & Technology)
A comparison was made of the adsorption properties towards o -phthalic acid of ND100 resin modified by oxygen groups and ND900 resin modified by amine groups. The work presented focused on various properties including adsorption under static equilibrium conditions, the adsorption thermodynamics and kinetics. In addition, a method was devised for the separation of o -phthalic acid from maleic acid and fumaric acid in wastewater. Two isotherm models (Langmuir and Freundlich) were used to fit the static adsorption results. Both equations fitted the experimental data perfectly. The kinetic results led to the conclusion that the adsorption of o -phthalic acid onto ND900 involved a type of chemical transition.